Androblastoma of the Ovary - Jha, M; Shakya, B (Nepal Journal of Obstetrics and Gynaecology, 2014)
Androblastoma of the ovary occurs most frequently in the 3rd to 4th decades of life and about 75% of the lesions are seen in women younger than 40 years. This tumor produces androgen and virilization is present in more than 70% of the patients. Due to the early diagnosis and treatment of such type of tumor, the prognosis is very good. This was a case report of an 18 years’ unmarried girl who presented with signs of virilization and amenorrhea for two years. On abdominal examination mass was up to epigastric reason, after all investigation we planned for laparotomy. Histopathology report revealed androblastoma of the ovary. After a month of operation, she had regular menstruation. DOI: http://dx.doi.org/10.3126/njog.v9i2.11765